1987
DOI: 10.1128/jvi.61.3.904-911.1987
|View full text |Cite
|
Sign up to set email alerts
|

Replication strategy of human hepatitis B virus

Abstract: To study the replication strategy of the human hepatitis B virus, the 5' end of the RNA pregenome and the initiation sites of DNA plus and minus strands have been mapped. The RNA pregenome was found to be terminally redundant by 120 nucleotides; it is initiated within the pre-C region and may also function as mRNA for synthesis of the major core protein and the hepatitis B virus reverse transcriptase. The hepatitis B virus DNA minus strand is initiated within the direct repeat sequence DR1, it contains a termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
1
3

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(139 citation statements)
references
References 34 publications
10
125
1
3
Order By: Relevance
“…A selection mechanism requiring neither an immunological nor a functional role for precore products may operate during HBV nucleocapsid assembly. Precore mRNA transcripts harbouring translation initiation mutations may escape discrimination that operates via the translational inactivation of transcripts initiating at the precore start codon [27][28][29] and may therefore be packaged more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…A selection mechanism requiring neither an immunological nor a functional role for precore products may operate during HBV nucleocapsid assembly. Precore mRNA transcripts harbouring translation initiation mutations may escape discrimination that operates via the translational inactivation of transcripts initiating at the precore start codon [27][28][29] and may therefore be packaged more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…These ORFs represent the gene sequences that encode the virus nucleocapsid (core) and envelope (surface) proteins as well as the virus replicase (polymerase) and a protein that appears to be involved in virus gene expression (X). Three major, unspliced messenger RNA (mRNA) transcripts are synthesized by a cell-derived RNA polymerase I1 (17). The longest, a 3.5-kilobase (kb) terminally redundant transcript, is used both as a template for genome replication by reverse transcription and as the mRNA for expression of the core and polymerase proteins.…”
Section: Overlapping Gene Sequencesmentioning
confidence: 99%
“…The most highly conserved nucleotide sequence of the HBV genome spans the pre-core and core ORFs. Termed the U5-like region for its homology to the 5'-unique region of retrovirus long terminal repeats (20,21), this region has been found to reside in the terminal repeats of the linear HBV RNA pre-genome (17). Within a 62nucleotide domain 54, or 87%, of the nucleotides are identical at a given position among 16 mammalian hepadnavirus genomes (Fig.…”
Section: Two Newly Identified Overlapping Open Reading Framesmentioning
confidence: 99%
“…It contains a number of inverted repeat sequences, which have the potential to form secondary, and possibly tertiary, structures that could be recognized in the packaging reaction [5]. Although both genomic transcripts of HBV contain ε near the 5′ end, only the shorter, viz, pgRNA, is encapsidated [5,[10][11][12] and reverse transcribed [13]. Nassal and co-workers [14] showed that translating 80S ribosomes advancing into ε prevent it from functioning and concluded that the ability of ε to be trans-lated is decisive in determining whether or not an εcontaining RNA is packaged.…”
Section: Introductionmentioning
confidence: 99%